Are Retirement Planning Tools Substitutes or Complements to Financial Capability? - Gopi Shah Goda; Matthew R. Levy; Colleen Flaherty Manchester; Aaron Sojourner; Joshua Tasoff; Jiusi Xiao (Institute of Labor Economics (IZA), 2022)
We conduct a randomized controlled trial to understand how a web-based retirement saving calculator affects workers' retirement-savings decisions. In both conditions, the calculator projects workers' retirement income goal. In the treatment condition, it also projects retirement income based on defined-contribution savings, prominently displays the gap between projected goal and actual retirement income, and allows users to interactively explore how alternative, future contribution choices would affect the gap. The treatment increased average annual retirement contributions by 174 (2.3 percent). However, effects were larger for those with greater financial knowledge, suggesting this type of tool complements, rather than substitutes for, underlying financial capability.
Keywords: D14; G53; J32; 330; retirement planning; retirement saving; exponential-growth bias; present bias; financial literacy; financial capability